Taxable and Tax-Deferred Investing with the Limited Use of Losses - Fischer, Marcel; Gallmeyer, Michael (Review of Finance, 2017)
Abstract We study the impact of the different tax treatment of capital gains and losses on the optimal location of assets in taxable and tax-deferred accounts. The classical result of Black (1980) and Tepper (1981) suggests that investors should follow a strict pecking order asset location rule and hold those assets that are subject to the highest tax rate preferentially in tax-deferred accounts. We show that with the different tax treatment of realized gains and losses, only tax-efficient equity mutual funds are optimally held in taxable accounts, whereas mutual funds with average tax-(in)efficiency are preferentially held in tax-deferred accounts.